Pengembangan E-LKM Berbasis Problem-Based Learning Pada Mata Kuliah Metode Statistika - Nurdalilah Nurdalilah; Ramadhani Ramadhani; Hizmi Wardani; Rizki Rindiani; Muhammad Farhan Fadilllah (Universitas Islam Jember, 2026)
The purpose of this research is to produce and develop E-LKM as a learning medium for the statistics course. The problem-based learning method was chosen because it increases student engagement and their understanding of statistical concepts through solving real-world problems. The process of developing E-LKM uses the PLOMP model, which consists of four stages. The research subjects are students III from the Mathematics Education semester at UMN Al-Washliyah, and the study involved a trial with a group of students. The research results show that the E-LKM statistical method is considered valid by content and media validators and is practical for use in learning. The results of using E-LKM show that E-LKM falls into the valid criteria with an average of 86.76%, and E-LKM is considered very practical in trials with an average of 83.34%. Therefore, the resulting E-LKM is valid, easy to use, and receives positive feedback Keywords: E-LKM, Problem-Based Learning, Statistical Methods